“Natural coordination” and the origin of the Lithuanian conjunction beĩ ‘and’ - Ostrowski, Norbert (Baltistica, 2017)
Productivity of the Lithuanian conjunction beĩ ‘and’, marker of so called „natural coordination”, is strictly connected to the area of Lithuania Minor (former East Prussia). Lithuanian beĩ comes from conflation of the common Baltic conjunction bè ‘and’ and an additive particle ir ‘also’. The conflated form *beir has been further reduced to beĩ in accordance with Lithuanian phonotactic rules that do not tolerate group VRR (V = Vocal, R = Resonant). There are some traces that suggest that Lithuanian beĩ ‘and’ came into existence in the bilingual, Old Prussian-Lithuanian environment.
Keywords: Lithuanian; Old Prussian; historical syntax; etymology; language contacts